2016
DOI: 10.1021/acs.nanolett.6b01795
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Sublattice Asymmetry in Pure and Boron-Doped Graphene

Abstract: The implementation of future graphene-based electronics is essentially restricted by the absence of a band gap in the electronic structure of graphene. Options of how to create a band gap in a reproducible and processing compatible manner are very limited at the moment. A promising approach for the graphene band gap engineering is to introduce a large-scale sublattice asymmetry. Using photoelectron diffraction and spectroscopy we have demonstrated a selective incorporation of boron impurities into only one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 43 publications
10
56
0
Order By: Relevance
“…11 More recently, by photoelectron diffraction measurements performed on the same system, a separation value between the two main components of about 270 meV has been estimated. 25 At the DFT-LDA level, the optimized Co-Gr distance for this configuration is found to be 2.05Å, in good agreement with existing literature. 17,24 The C1s core-level shifts computed for these two C sites differ by about 180 meV.…”
Section: Xps Of Flat Graphene @ Cosupporting
confidence: 86%
See 1 more Smart Citation
“…11 More recently, by photoelectron diffraction measurements performed on the same system, a separation value between the two main components of about 270 meV has been estimated. 25 At the DFT-LDA level, the optimized Co-Gr distance for this configuration is found to be 2.05Å, in good agreement with existing literature. 17,24 The C1s core-level shifts computed for these two C sites differ by about 180 meV.…”
Section: Xps Of Flat Graphene @ Cosupporting
confidence: 86%
“…The splitting between these two peaks had been previously computed within the initial states approximation in Ref. 25 (ISA), where a larger value of 350 meV was found. This discrepancy can be explained by the fact that ISA neglects relaxation effects of the valence and core electrons upon ionization of the core.…”
Section: Xps Of Flat Graphene @ Comentioning
confidence: 64%
“…In general, this occurs if the impurities are randomly located in sites corresponding to the sub-lattice LS and therefore they do not contribute to the electronic transport. Thus, the recent reported phenomenon [23][24][25][26] in which doping occurs asymmetrically between the two sublattices (A and B) is a current interesting topic related to our work.…”
Section: Introductionmentioning
confidence: 71%
“…They reported the chemical structure of the doped sheets changed from a disordered (less π-conjugated) state with a B-puckered configuration at 600 to 800 • C to an ordered (highly π-conjugated) state with a planar configuration at 1500 • C. The planar graphitic layers were reported to accommodate <3% of B content, while the amorphous, BC x -like materials exhibited much higher surface areas (500 to 800 m 2 /g) and 12% B content with electron-deficient B moieties, resulting in enhanced H 2 binding energies (-12 to −20 kJ/mol at higher coverage). In a recent joint experimental and computational effort [33], a site-specific selective incorporation of B into the graphene sublattices was demonstrated to form a tunable band gap controlled by the dopant concentration. Shcherban et al [34] reported a nanocasting approach to prepare B-doped CMK-3 using SBA-15 as an exo-template.…”
Section: Introductionmentioning
confidence: 99%